Epilepsy and coeliac disease. Issue 8 (August 1982) - Hanly, JG; Stassen, W; Whelton, M; Callaghan, N
Abstract : A number of neurological disorders have been described in association with coeliac disease, including epilepsy. A review of 177 patients with coeliac disease failed to show an increased prevalence of epilepsy. This is contrary to the findings of other workers, and requires further investigation.